Customer satisfaction levels of service quality at ar-Rahnu, Kelantan - Othman, Azizah; Hashim, Norashidah; Abdullah, Syahrina (2012)
This research was conducted to verify levels of customer satisfaction and service quality for the pawn-broking company Ar-Rahnu in Kelantan, Malaysia. Three hundred (300) respondents were selected by choosing the sample through simple sampling or by quota sampling. The instrument used to collect the data was by a questionnaire that was filled out by the respondents and collected back on the same day. The information collected was analysed using inferential and descriptive methods. The descriptive analysis showed that the majority of the respondents were married women, 30-39 years old. The majority of the respondents also had an education level until secondary school (high school), but only 38% had an education level until diploma or degree. Most of the respondents were traders and made less than RM1000.00 per month. The main factor that motivated the respondents to obtain Ar-Rahnu services was that the company could handle problems that were not expected. Statistical methods showed that service quality at Ar-Rahnu Kelantan and Ar-Rahnu Bank Rakyat services is high. The research may show the level of service quality prepared by the Ar-Rahnu organizations but the organizing and implementation within society helps many people, primarily in time of emergencies and in the need for cash quickly. It is hoped that much more research can be done on Ar-Rahnu, but from different aspects.